2015
DOI: 10.1007/s13105-015-0389-9
|View full text |Cite
|
Sign up to set email alerts
|

Orosomucoid, an acute response protein with multiple modulating activities

Abstract: Orosomucoid (ORM), or alpha-1-acid glycoprotein (AGP), is one of the acute-phase proteins. It has a molecular weight of 37-54 kDa, low pI of 2.8-3.8, and is heavily glycosylated (45 %). It is mainly synthesized by the liver, but many extrahepatic tissues have also been reported to produce ORM under myriad physiological and pathological conditions. Expression of the ORM gene is mainly controlled by a combination of the major regulatory mediators, such as glucocorticoids, interleukin (IL)-1, TNF-α, and IL-6. ORM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
174
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(180 citation statements)
references
References 80 publications
3
174
0
3
Order By: Relevance
“…Analyses were motivated by a recent molecular profiling study that assessed the association of 106 metabolites with mortality and found AGP to have the strongest association with all-cause mortality. 9 Because AGP is an acutephase protein that is not widely measured, 15 we compared its ability to predict mortality with the more commonly measured inflammatory biomarkers IL-6 and CRP. Our results showed that AGP was indeed associated with all-cause and cancer-related mortality in the short term; however, it was not associated with mortality beyond 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses were motivated by a recent molecular profiling study that assessed the association of 106 metabolites with mortality and found AGP to have the strongest association with all-cause mortality. 9 Because AGP is an acutephase protein that is not widely measured, 15 we compared its ability to predict mortality with the more commonly measured inflammatory biomarkers IL-6 and CRP. Our results showed that AGP was indeed associated with all-cause and cancer-related mortality in the short term; however, it was not associated with mortality beyond 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…There are two isoforms of ORM in human (ORM1 and ORM2), one isoform in rat (ORM), and three isoforms in mouse (ORM1, ORM2, and ORM3) (14). These genes have an identical structure with six exons and five introns.…”
mentioning
confidence: 99%
“…Although it is mainly synthesized by the liver, many extrahepatic tissues, including adipocytes, heart, and brain, are capable of producing ORM under myriad physiological and pathological conditions (16)(17)(18)(19). A variety of activities have been attributed to ORM, which include modulating immunity, carrying drugs, maintaining the capillary barrier, and mediating sphingolipid metabolism (14,(20)(21)(22)(23). It has been reported that the effects of ORM on macrophages, neutrophils, and liver parenchymal cells are mediated by membrane receptor CCR5, Siglect-5, and hemoglobin b-chain, respectively (24)(25)(26).…”
mentioning
confidence: 99%
“…Orosomucoid, an acute phase protein, is available in some laboratories [11] . Ferritin, a measure of iron stores, is also an acute phase protein, increasing with CRP in the setting of acute infection or inflammation [12] .…”
Section: Discussionmentioning
confidence: 99%